(untitled) (Research, Society and Development, 2023)
The present study addresses the issue related to smoking and the relationship with oral cancer, focusing on the role of the Dentist. Thus, the present study has the following problem: What is the dentist’s approach regarding the relationship between smoking and the appearance of oral cancer? Its general objective was to expose the role of the dentist in the relationship between smoking and oral cancer, while the specific objectives aimed to characterize oral cancer, highlight the risk factors of smoking and oral cancer and the consequences for people’s health and explain the role of the Dentist in the prevention of smoking and its behavior in relation to oral cancer rates. With regard to Dentistry, the topic is of great relevance since part of the population, despite knowing that smoking is harmful to health, still insists on this practice, requiring the intervention of health professionals in which the Dentist is present. in a multidisciplinary team creating mechanisms. which will contribute to improving oral cancer prevention mechanisms, reducing this dependence, thus carrying out health education work that could, ultimately, create conditions to improve people’s quality of life.